2015
DOI: 10.1098/rsta.2013.0152
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis seen in action

Abstract: Synchrotron radiation techniques are widely applied in materials research and heterogeneous catalysis. In homogeneous catalysis, its use so far is rather limited despite its high potential. Here, insights in the strengths and limitations of X-ray spectroscopy technique in the field of homogeneous catalysis are given, including new technique developments. A relevant homogeneous catalyst, used in the industrially important selective oligomerization of ethene, is taken as a worked-out example. Emphasis is placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19] The experimental tools have progressed enormously in the last years, allowing to investigate catalysts in action, even in extreme conditions (high temperature, high pressure, etc.) and with increasing time-and space-resolution.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] The experimental tools have progressed enormously in the last years, allowing to investigate catalysts in action, even in extreme conditions (high temperature, high pressure, etc.) and with increasing time-and space-resolution.…”
Section: Introductionmentioning
confidence: 99%
“…As we have commented, SR techniques have proved especially powerful in catalytic science. The article of Tromp [1] gives a number of elegant examples of how XAS techniques, in conjunction with other spectroscopies, have given atomic-level insight into the operation of predominantly homogeneous, industrial catalytic systems. Recent examples of the power of these techniques are also shown by the work of Brookes et al [19], who have used XAS to probe the widely used iron-molybdate heterogeneous catalyst (used in the selective oxidation of methanol to formaldehyde, which is of significant industrial importance) and with input from computational modelling have developed a model, shown in figure 1 for the active site of this widely studied system, which comprises an MoO 3 formula unit supported on Fe 2 O 3 .…”
Section: Materials Chemistrymentioning
confidence: 99%
“…Their ability to obtain accurate information at the atomic and molecular level on both local and longrange structures, together with the increasing ability to undertake time-resolved structural studies, has transformed our understanding of several key classes of functional material, while their power as analytical probes has a major influence on aspects of environmental science. Beamlines at the Diamond Light Source continue to make a major contribution to these fields, which are briefly reviewed in this article and which are clearly exemplified in the papers of Tromp [1] and Burke et al [2].…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, a certain number of achievements have been accumulated along more than 60 years of academic research, and we are confident that at least part of them have been and still are useful for industrial researchers. Only recently, and quite late in comparison to other fields in catalysis, the operando approach (i.e., measurements performed in conditions as close as possible to the industrial process) showed its appearance in the investigation of the Phillips catalyst. Although still at its infancy, this approach has already led to important discoveries.…”
Section: Introductionmentioning
confidence: 99%